2004
DOI: 10.1596/1813-9450-3254
|View full text |Cite
|
Sign up to set email alerts
|

Decentralization or Fiscal Autonomy? What Does Really Matter? Effects on Growth and Public Sector Size in European Transition Countries

Abstract: This paper examines the importance of fiscal autonomy in the analysis of decentralization. Using new data published by the OECD (2001, 2002), it reproduces several indicators and proposes new measures of decentralization that take into consideration subnational governments' autonomy over their revenues. Two models are reproduced: Davoodi and Zou (1998) on decentralization and economic growth, and Oates (1985), on decentralization and public sector size. Some evidence suggests that fiscal autonomy positively af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Better roads, higher standards of schools and more effective health services can be provided. In other words, decentralization contributes to economic growth and development if it provides more efficiency in allocating (Meloche et al, 2004, p. 3, USAID, 2005. In addition, it is seen that decision-making by the central administration in education service prolongs bureaucratic procedures and it can be said that it prevents decision making in accordance with citizen preferences.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Better roads, higher standards of schools and more effective health services can be provided. In other words, decentralization contributes to economic growth and development if it provides more efficiency in allocating (Meloche et al, 2004, p. 3, USAID, 2005. In addition, it is seen that decision-making by the central administration in education service prolongs bureaucratic procedures and it can be said that it prevents decision making in accordance with citizen preferences.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The fiscal sufficiency is generally regarded as the key factor in the division of fiscal power in China (Chen et al., 2016). A review of existing empirical studies shows that the “fiscal autonomy” has been used as a common measure of fiscal sufficiency, and is measured as the percentage of the revenue of a local region to its total expenditure (Huang, 2019; Jiao, 2020), or as the ratio of local fiscal revenue to its total revenue (Ebel & Yilmaz, 2002; Meloche et al., 2004). The “fiscal comfort level” also has been used to measure local fiscal sufficiency, measured by the ratio of local revenue index to expenditure demand index (Cowan, 1997).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The literature on the relationship between fiscal federalism and economic activities is vast and mixed: some studies found a clear positive relationship, e.g., [20][21][22][23][24][25][26]; some found negative relationships, e.g., [27][28][29][30][31]; while several others found no relationship at all, e.g., [32]. Traditional literature on fiscal federalism [6][7][8][9]12,33] posit that fiscal decentralization has a positive effect on economic activities.…”
Section: Literature Reviewmentioning
confidence: 99%